Evaluating the Effect of Extrinsic and Intrinsic Rewards on Job Performance: The Mediating Role of Job Satisfaction - Marahastuti, Kristiana; Haryono, Siswoyo; Nuryakin (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of extrinsic and intrinsic rewards on performance mediated by job satisfaction. This research is explanative quantitative research. The population of this research is the employee of the Agriculture and Food Service Office of Kebumen Regency, Central Java, who is a State Civil Apparatus (ASN). The sampling technique uses purposive sampling. The instrument uses questionnaires and observations. Data analysis was on the results of instruments that were valid and reliable. Data analysis techniques using the Structural Equation Modeling (SEM) method using AMOS 24.00. The results showed that extrinsic and intrinsic rewards had a positive and significant effect on employee satisfaction and performance. Other results indicate that employee job satisfaction has a positive and significant effect on employee performance. Job satisfaction does not act as a mediator on the effect of extrinsic rewards on performance but instead acts as a mediator on the effect of intrinsic rewards on performance. In the analysis of total influence shows that intrinsic rewards have a more considerable influence on improving employee performance.